ChemInform Abstract: Organocatalytic One‐Pot 1, 4‐/1, 6‐/1, 2‐Addition Sequence for the Stereocontrolled Formation of Six Consecutive Stereocenters. Issue 26 (June 2015) - Chauhan, Pankaj; Mahajan, Suruchi; Raabe, Gerhard; Enders, Dieter
Abstract An unprecedented, highly efficient synthesis of oxazoles bearing cyclohexanes is presented in an excellent diastereo‐ and enantioselective manner.